TWO NEW RECORDS OF MACTRID BIVALVES (BIVALVIA: MACTRIDAE) FROM INDONESIA - Reni Ambarwati; Trijoko (BRIN Publishing (Penerbit BRIN), 2015)
The occurrence of two mactrid bivalves, Mactra (Mactra) queenslandica E.A. Smith and Heterocardia gibbosula Stoliczka, in coastal water of Sidoarjo, East Java, Indonesia is reported here. They are described and illustrated based on the local specimens collected. Previously, the distribution of M. queenslandica was reported only from northern-north-east Australia. This finding revealed that the distribution of this bivalve reaches Indonesia waters. Meanwhile, H. gibbosula is common in south-east Asian waters, however this is the first record for Indonesian waters. This result indicated that more mactrid bivalves could be discovered in Indonesian waters.